Forbidden love a harrowing true story of love and revenge in Jordan - Khouri, Norma (Bantam Books, 2003)
Dalia was a young, beautiful, Arabian Muslim living with her family in Amman, Jordan. This text gives a harrowing account by a Jordanian woman of the honour-killing of her lifelong friend at the hands of her own father, after she fell in love with a young Catholic man.